8.2 Cardiac Ion Channelopathies in Unexplained Stillbirths. (9th June 2014) - Addison, S; Munroe, PB; Mein, C; Cohen, M; Fowler, D; Sebire, NJ; Peebles, D; Taylor, AM; Abrams, D; Thayyil, S
Abstract : Background: Although cardiac ion channelopathies are reported in up to 15% of sudden infant deaths, the prevalence in unexplained stillbirths is not known. Objective: To determine the prevalence of genetic mutations in cardiac ion channels in unexplained stillbirths. Design/Methods: We examined post-mortem tissue (muscle or heart) samples from 46 unexplained stillbirths (gestation 22–42 weeks), where no cause of death could be identified after a detailed autopsy which included examination of the placenta. Following extraction of deoxyribose nucleic acid, we performed mutational analysis for 35 genes, including 12 genes causing inherited long and short QT, and both published and non-published genes discovered using genome-wide association studies (GWAS) of QT and sudden cardiac death, using next generation sequencing (Illumina MiSeq Sequencing Platform). Bioinformatics analysis was performed on all variants using SIFT functional prediction, PolyPhen functional prediction, Conservation PhyloP p-value and Annovar mutation prediction software, to identify the most functionally significant variants. Results: In total 11 variants, three in LQT genes ( AKAP9, KCNJ2, KCNE2 ) and four in GWAS genes ( BAZ2B, RYR2, TRPM7, CAV2 ), were predicted to be functionally damaging. One or more of these variants were seen in 29 of the 46 cases. Conclusions: Genetic variants predicted to be functionally damaging are seen in 63% of the unexplained stillbirths in this study. As these variants are rare and novel or have no functional data, functional testing is required to examine the clinical significance.